2023
DOI: 10.3389/fmicb.2023.1192832
|View full text |Cite
|
Sign up to set email alerts
|

Viable SARS-CoV-2 Omicron sub-variants isolated from autopsy tissues

Santiago Maffia-Bizzozero,
Cintia Cevallos,
Federico Remes Lenicov
et al.

Abstract: IntroductionPulmonary and extrapulmonary manifestations have been described after infection with SARS-CoV-2, the causative agent of coronavirus disease 2019 (COVID-19). The virus is known to persist in multiple organs due to its tropism for several tissues. However, previous reports were unable to provide definitive information about whether the virus is viable and transmissible. It has been hypothesized that the persisting reservoirs of SARS-CoV-2 in tissues could be one of the multiple potentially overlappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Although the link between viral persistence and long COVID may not be causal, these results suggest that persistent infections could be contributing to the pathophysiology of long COVID 10 , 45 , as also evidenced by the observation of circulating SARS-CoV-2 S1 spike protein in a subset of patients with long COVID months after first infection 46 . There is also a growing body of evidence of the persistence of replication-competent virus throughout the body months after the start of an infection 47 , 48 , and very recently that this persistence is strongly associated with higher risk of long COVID 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the link between viral persistence and long COVID may not be causal, these results suggest that persistent infections could be contributing to the pathophysiology of long COVID 10 , 45 , as also evidenced by the observation of circulating SARS-CoV-2 S1 spike protein in a subset of patients with long COVID months after first infection 46 . There is also a growing body of evidence of the persistence of replication-competent virus throughout the body months after the start of an infection 47 , 48 , and very recently that this persistence is strongly associated with higher risk of long COVID 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been highlighted in the specialized literature. A study from Argentina observed increased positivity and persistence of the viral genome in the study cohort for up to 22 days from onset [ 46 ]. A cohort study demonstrates the presence of the viral genome in the lungs even after 67 days [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is plausible to suggest that platelets, and megakaryocytes ( 23 ), may contribute to the dissemination of the virus, which first affects the lungs and then spreads via the blood stream, infecting various organs and tissues. A recent study has shown that Omicron can indeed spread to multiple tissue locations after primary infection ( 54 ). The mechanisms by which the virus enters platelets and megakaryocytes remain unclear, but besides a low ACE2 expression, several candidates for SARS-CoV-2 receptors have been proposed ( 34 ), including GPIb ( 55 ) and CD147 ( 49 ).…”
Section: Discussionmentioning
confidence: 99%